Perceptions of Emotional Functionality: Similarities and Differences Among Dignity, Face, and Honor Cultures. (April 2022) - Maitner, Angela T.; DeCoster, Jamie; Andersson, Per A.; Eriksson, Kimmo; Sherbaji, Sara; Giner-Sorolla, Roger; Mackie, Diane M.; Aveyard, Mark; Claypool, Heather M.; Crisp, Richard J.; Gritskov, Vladimir; Habjan, Kristina; et al.
Emotions are linked to wide sets of action tendencies, and it can be difficult to predict which specific action tendency will be motivated or indulged in response to individual experiences of emotion. Building on a functional perspective of emotion, we investigate whether anger and shame connect to different behavioral intentions in dignity, face, and honor cultures. Using simple animations that showed perpetrators taking resources from victims, we conducted two studies across eleven countries investigating the extent to which participants expected victims to feel anger and shame, how they thought victims should respond to such violations, and how expectations of emotions were affected by enacted behavior. Across cultures, anger was associated with desires to reclaim resources or alert others to the violation. In face and honor cultures, but not dignity cultures, shame was associated with the desire for aggressive retaliation. However, we found that when victims indulged motivationally-relevant behavior, expected anger and shame were reduced, and satisfaction increased, in similar ways across cultures. Results suggest similarities and differences in expectations of how emotions functionally elicit behavioral responses across cultures.